INCIDENCE OF SEPSIS IN CHILDREN UNDER 5 YEARS OLD WITHIN KIRKUK PROVINCE - Bazzaz, Ayoub A.; Rana W. Al-Hassan; A. Yassin; Noorhan A. Chelebi (Journal of Medical Genetics and Clinical Biology, 2025)
Objectives: Medical researches on septicemia, particularly, in most susceptible age group of children i.e. newborns and young infants in Iraq are scanty. The aim of this study is to assess the incidence of blood poisoning via hematological parameters in children under 5 years old within Kirkuk Province. Methodology: Only 120 children aged 1-60 months admitted to hospital on suspicion of blood poisoning were selected and compared with other 40 healthy children of similar ages used as control. Results: Almost 42.5% of suspected cases admitted to hospital were diagnosed sepsis positive. Over 80% of affected sepsis cases were in children aged 1-18 months old but dropped down as the age advanced. The main blood parameters i.e. leucocytes (WBC), erythrocytes (RBC), hemoglobin (Hb%), Lymphocytes (L), Blood platelets (PLT) were significantly (p≤0.05-0.0001) affected up and down in sepsis patients in comparison with counterpart children. Novelty: It is concluded that the newborn and infants are more susceptible to infection than older ages due to the immaturity of the immune system in these babies, artificial rather than breast feeding, negligence and inexperience of mothers and deficiency of hygienic parameters applied. Early and regular health checkup of newborn babies under 5 years old by pediatricians deems mandatory to promote health measurements and reduce children mortality.